Using non-vitamin K oral anticoagulants in specific patient populations: a study of Korean cases - Cho IY (Dove Medical Press, 2019)
Il Young Cho1,2 1College of Pharmacy, Ewhawomans University, Seoul, Republic of Korea; 2Pharmaceutical Safety Bureau, Ministry of Food and Drug Safety, Cheongju-si, Republic of KoreaCorrespondence: Il Young ChoPharmaceutical Safety Bureau, Ministry of Food and Drug Safety, 187, Osongsaengmyeong 2-ro, Osong-eup, Heungdeok-gu, Cheongju-si, Chungcheongbuk-do 28159, Republic of KoreaTel +82 43 719 2709Fax +82 43 719 2700Email iycho10@korea.krAbstract: Non-vitamin K oral anticoagulants (NOACs) are increasingly used as alternatives to conventional therapies and have considerable accumulated real-world clinical data in patients with non-valvular atrial fibrillation (NVAF) or venous thromboembolism (VTE). However, it is not easy to make a complete changeover to NOACs in real-world clinical practice because NOACs still have challenges in specific patient populations (eg, Asian patients, NVAF patients presenting with acute coronary syndrome [ACS], dialysis patients with NVAF, patients with cancer-associated VTE, etc.). Clinical data on the optimal dose of NOACs in Asian patients with NVAF are not sufficient. The intensity of NOAC and antiplatelet treatment and the duration of antiplatelet treatment should be adjusted according to the bleeding and thrombotic risk profiles of the individual NVAF patient presenting with ACS. Increased bleeding risk and unclear efficacy of NOACs in dialysis patients with NVAF should be considered when making decisions on whether to give NOACs for these patients. If dialysis patients with NVAF require anticoagulant for stroke prevention, then apixaban could be considered while awaiting more clinical efficacy and safety data. Additional studies are needed to determine the utility of continuing treatment with reduced-dose NOACs for long-term therapy after VTE. We have enough experiences in using NOACs in cancer patients showing the benefit of antithrombotic treatment counterbalanced the bleeding risk; however, some challenges of cancer-associated VTE management exist due to differences in cancer types or chemotherapy regimens and comorbidities. Different dosing regimens among NOACs may impact on medication adherence; thus, individual patient preference should be considered in choosing a particular NOAC. A significant proportion of patients remain on warfarin because of the high price of NOACs and variability in reimbursement coverage. To compensate clinical-evidence and achieve optimal use of NOACs, we should pay attention to the outcomes of ongoing studies and evaluate more real-world data.Keywords: non-valvular atrial fibrillation, venous thromboembolism, risk management plan, optimal dose, drug price, cost-effectiveness